Transcriptomic Differences Between Human Trabecular Meshwork Stem Cells and Trabecular Meshwork Cells Reveal Specific Biomarker Profiles - Rong Du; Ajay Kumar; Enzhi Yang; Jingxue Zhang; Ningli Wang; Yiqin Du (Current Issues in Molecular Biology)
Glaucoma is a leading cause of irreversible blindness, normally associated with dysfunction and degeneration of the trabecular meshwork (TM) as the primary cause. Trabecular meshwork stem cells (TMSCs) have emerged as promising candidates for TM regeneration toward glaucoma therapies, yet their molecular characteristics remain poorly defined. In this study, we performed a comprehensive transcriptomic comparison of human TMSCs and human TM cells (TMCs) using RNA sequencing and microarray analyses, followed by qPCR validation. A total of 465 differentially expressed genes were identified, with 254 upregulated in TMSCs and 211 in TMCs. A functional enrichment analysis revealed that TMSCs are associated with development, immune signaling, and extracellular matrix remodeling pathways, while TMCs are enriched in structural, contractile, and adhesion-related functions. A network topology analysis identified CXCL3, CXCL6, and BMP2 as robust TMSC-specific hub genes, and LMOD1 and BGN as TMC-specific markers, with expression patterns confirmed by qPCR. These findings define distinct molecular signatures of TMSCs and TMCs, providing reliable biomarkers for cell identity and a foundation for future stem cell-based therapies targeting TM dysfunction in glaucoma.